2020
DOI: 10.2174/1871530320666200511012142
|View full text |Cite
|
Sign up to set email alerts
|

COX and PTGDS Gene Expression Levels in PGD2 Synthesis Pathway are Correlated with miR-520 in Patients with Vessel Restenosis

Abstract: Background: The vessel restenosis is related to the inflammatory events in subendothelial space. It is proposed that the inflammatory agents affect the prostaglandin synthesis pathway. In this study, we investigated the COX-1, COX-2, PTGDS and miRNA-520a-5p expression levels and the serum 15-Deoxy-∆ 12,14 –PGJ2 metabolite values in patients with the stenosed and re-stenosed vessels. Furthermore, the associations between genes and miR-520 were evaluated in the monocyte transfection studies. Methods: The subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…PTGDS can restrain vascular smooth muscle cell proliferation and migration [ 35 , 36 ]. Rezaee et al reported that PTGDS overexpression is thought to be a negative compensatory reaction to the inflammatory events elevated by prostaglandins because of its anti-inflammatory properties [ 37 ]. In addition, the changes in the expression levels of PTGDS are opposite to the expression levels of miR-520 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTGDS can restrain vascular smooth muscle cell proliferation and migration [ 35 , 36 ]. Rezaee et al reported that PTGDS overexpression is thought to be a negative compensatory reaction to the inflammatory events elevated by prostaglandins because of its anti-inflammatory properties [ 37 ]. In addition, the changes in the expression levels of PTGDS are opposite to the expression levels of miR-520 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rezaee et al reported that PTGDS overexpression is thought to be a negative compensatory reaction to the inflammatory events elevated by prostaglandins because of its anti-inflammatory properties [ 37 ]. In addition, the changes in the expression levels of PTGDS are opposite to the expression levels of miR-520 [ 37 ]. Therefore, this research suggested that PTGDS is a circulating marker for cardiovascular injuries and the severity of CAD.…”
Section: Discussionmentioning
confidence: 99%
“…We created a network comprising five miRNAs (mir-520a-5p, mir-876-5p, mir-346, mir-193a-3p, and mir-1224-5p) and four diagnostic biomarkers (C1orf105, CCL22, FRK, and GAP43). Shima et al reported that miR-520 found in vascular stenosis was negatively correlated with COX-1 and PTGDS gene expression levels [ 43 ]. TGP inhibits MSU-induced inflammation in THP-1 macrophages by modulating the MALAT1/miR-876-5p/NLRP3 axis [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a neuromodulator and trophic factor, PGD2 plays a key role in the central nervous system ( 17 ). Moreover, smooth muscle contraction and relaxation are also controlled by PGD2, and platelet aggregation is inhibited by it ( 18 ). Interestingly, the expression of this gene increased after the patient was given supportive care.…”
Section: Discussionmentioning
confidence: 99%